Cruise tourism exteralities and residents' support: A mixed approach - Juan Gabriel Brida; Giacomo Del Chiappa; Marta Meleddu; Manuela Pulina (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
This paper investigates residents' preferences of investment in cruise tourism, taking its externalities into full account. The research involved data collection in the port of call of Messina (Sicily, Italy), during the peak cruise season in 2011. A mixed generalized ordered logit analysis, based upon a correspondence analysis, is run to examine what factors influence residents' perceptions about investing in cruise tourism. Potential positive and negative externalities produced by this economic activity, as well as socio-demographic and economic determinants are taken into account. Overall, residents in Messina, treated as a composite stakeholder, would invest a very high level of resources in cruising if their income depends on the cruise activity, if they had a cruise trip in the past, if they belong to a family with a high number of components, and if they believe this activity to exert positive welfare, cultural and social externalities. Conversely, residents in Messina are likely to prefer a low, or very low level of investment the farther they live from the port, if they are female, retired and if they perceive a deterioration of the environment. Implications for policy makers are drawn from these empirical findings.
Keywords: C25; D62; L83; 330; cruise port of call; residents' support; externalities; correspondence analysis; generalized ordered logit